Seismic behavior and improvement of autoclaved aerated concrete infill walls. (15th August 2019) - Binici, Baris; Canbay, Erdem; Aldemir, Alper; Demirel, Ismail Ozan; Uzgan, Ugur; Eryurtlu, Zafer; Bulbul, Koray; Yakut, Ahmet
Highlights: Nine one-bay-one-story frames were tested under reversed cyclic lateral displacement excursions. The combined in-plane and out-of-plane response of AAC infilled frames were investigated. The in-plane drift capacity were found to be significantly reduced by the out-of-plane loads. A new system was tested to eliminate the interaction between the frame and AAC infill walls. Abstract: Performance of infill walls in reinforced concrete (RC) frames is generally questionable under the combined action of in-plane and out-of-plane seismic demands. Despite the vast number of tests investigating the behavior of brick masonry infill walls in RC frames, past research is limited for infill walls made of Autoclaved Aerated Concrete (AAC) blocks. In the first part of the study, six single-bay single-story half-scaled RC frames were tested under the action of in-plane cyclic displacement excursions and/or out-of-plane pressure. It was found that the presence of out-of-plane pressure can significantly reduce the deformation capacity of RC framed AAC infill walls. Afterwards, a new innovative system is proposed to protect the infill walls from in-plane induced forces while providing out-of-plane support. Sliding connectors placed inside the AAC blocks were used to isolate the infill wall from earthquake-induced frame deformations, while providing out-of-plane support. In order to test the beneficial effect of the proposed system, three additional tests were conducted. The proposed system managed to reach in-plane deformation demand of 2% without cracking and preserving its out-of-plane stability.